2013
DOI: 10.1111/pim.12045
|View full text |Cite
|
Sign up to set email alerts
|

A co‐infection with two gastrointestinal nematodes alters host immune responses and only partially parasite dynamics

Abstract: Given their global distribution and abilities to persist in the host, helminths can play a crucial role in affecting risk of infections by increasing individual variation in infection. Helminth co-infections are of particular interest because by altering host immune responses, they can modify host susceptibility and thus intensity and transmission of other parasites/pathogens. The dynamics of co-infection were examined using two helminths of the European rabbit. Individuals were simultaneously challenged with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(65 citation statements)
references
References 30 publications
(74 reference statements)
4
61
0
Order By: Relevance
“…These contrasting dynamics can be captured within the rabbit-helminth system. We have shown experimentally that T. retortaeformis is reduced or cleared in older hosts by a strong type 1-type 2-acquired immune response, whereas G. strigosum persists with high abundances despite a type 2 immune reaction typical to helminths (28,29,38). Our model framework assumes that host susceptibility and helminth establishment are affected by immunity and/or parasite intensity dependence.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…These contrasting dynamics can be captured within the rabbit-helminth system. We have shown experimentally that T. retortaeformis is reduced or cleared in older hosts by a strong type 1-type 2-acquired immune response, whereas G. strigosum persists with high abundances despite a type 2 immune reaction typical to helminths (28,29,38). Our model framework assumes that host susceptibility and helminth establishment are affected by immunity and/or parasite intensity dependence.…”
Section: Significancementioning
confidence: 99%
“…and yet the parasites show contrasting infection dynamics (26,27) and a distinct response to host immunity (28,29). Additionally, the system is under the influence of climate warming (30,31) and a strong seasonal regime (26,27,32) (Fig.…”
Section: Significancementioning
confidence: 99%
“…While there is some variability in the immune response between rabbits (Murphy et al, 2011(Murphy et al, , 2013Cattadori et al, 2013), the effect of this variability on egg hatchability will be addressed in a different study. To address our aims, we infected a single rabbit for each species and followed the hatching success of eggs produced by a cohort of parasites of the same age exposed to an immune response that changed over the course of the trial.…”
Section: Experimental Designmentioning
confidence: 99%
“…Trichostrongylus retortaeformis and G. strigosum are directly transmitted nematodes that colonize the small intestine and stomach, respectively, of the European rabbit (Oryctolagus cuniculus). We recently showed that rabbits mount a strong immune response to both nematodes by targeting third-stage larvae, adult worms and adult excretory/secretory compounds (Murphy et al, 2011(Murphy et al, , 2013Pathak et al, 2012;Cattadori et al, 2013). What determined this different pattern is unclear, since eggs of both parasites were exposed to identical environmental conditions in the laboratory and the field.…”
Section: Introductionmentioning
confidence: 99%
“…As data on within-host community dynamics of parasites are beginning to emerge (Murphy et al 2013; Telfer et al 2010), models are needed to explore both the within-host assembly process and how this process affects host population dynamics. Earlier work on population dynamics of parasite communities (e.g., Dobson and Roberts 1994) emphasized the importance of aggregated distributions of parasite species within different host individuals in determining population-level parasite coexistence.…”
Section: Introductionmentioning
confidence: 99%